2023
DOI: 10.53550/eec.2023.v29i03s.084
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation within the melatonin receptor 1C (MTNR1C) gene in the native chicken ‘Zo-ar’ of Mizoram, India

Abstract: The study has been aimed to uncover the presence of polymorphism within the MTNR1C gene in native chicken population, ‘Zo-ar’ of the Mizoram state of India and to calculate the allelic and genotypic frequency to screen the variation present within the population with respect to the MTNR1C gene which is associated with various egg production traits in poultry. DNA extraction has been done with the help of blood samples collected from a total of 50 randomly chosen ‘Zo-ar’ chicken irrespective of age or sex from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The RFLP method used in this study determined that the size of the DNA fragment from the MTNR1C (372 bp) and NPY (240 bp) genes was the same as that reported by Israa et al (2021) and Bora et al (2023). Moreover, there are three genotypes of the MTNR1C gene in chickens: AA, AG, and GG, with AG having the greatest genotype frequency.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The RFLP method used in this study determined that the size of the DNA fragment from the MTNR1C (372 bp) and NPY (240 bp) genes was the same as that reported by Israa et al (2021) and Bora et al (2023). Moreover, there are three genotypes of the MTNR1C gene in chickens: AA, AG, and GG, with AG having the greatest genotype frequency.…”
Section: Discussionsupporting
confidence: 74%
“…According to Israa et al (2021), in local Iraqi chicken, heterozygous genotypes of MTNR1C gene are more common than homozygous genotypes. Bora et al (2023) found two genotypes (AG and GG) for the MT-NR1C gene in the Zo-ar chicken population, with the G allele being predominantly present. The genotype frequencies for the bb variant of the NPY gene in this study were found to be significantly different from those previously observed in native chickens from Mazandaran and local brown chickens from Iraq.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations